Diseño de un sistema de alcantarillado combinado y agua potable para la Urbanización El Capulí, ubicado en el barrio El Capulí, parroquia de Tambillo, cantón Mejía, provincia de Pichincha - Rodríguez Quinatoa, Lourdes Trinidad (2017)
The growth of the population in urban areas of the Tambillo town has required the development of urban housing projects in the rural areas of this town, so it is essential to provide basic water and sewage systems. The objective of this project is to provide basic systems such as: drinking water and combined sewerage, which will ensure a better quality of life of the population to which it will serve, for this standar and technical specifications must be followed. In the pre-feasibility phase, it was proposed two alternatives for sewage system (separate and combined), and for drinking water analysis of the distribution of drinking water was done. For this, it’s necessary to obtain the minimum studies of topography, hydrological and hydraulic information, geological and geotechnical information, structural analysis and environmental impact studies. For the sewage system, the technical and economic comparison of the alternatives to choose the most appropriate and the best for the project was analyzed. The chosen alternative is a combined sewage system for the El Capulí urbanization which drains into the El Belen ravine, but previously the wastewater will be treated through a treatment plant that consists of a septic tank, sludge drying bed and anaerobic filter flow rate. For the execution of the project it is necessary to invest US $ 679177.59. The economic analysis indicated that this project is viable, because the economic indicators obtained were positive.